Perancangan Sistem Informasi Absensi Berbasis Web dengan Validasi Lokasi Pada PT XYZ - Fakhri Alauddin Tarihoran; Much Nur Syams Simaja; Raissa Amanda Putri (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
Employee attendance plays an important role in maintaining discipline and supporting work effectiveness. However, manual and fingerprint-based attendance systems still face several challenges, such as the possibility of proxy attendance, long queues during check-in hours, and difficulties in data recap. To address these issues, this study designs a web-based attendance information system equipped with GPS location validation and photo capture as proof of attendance. The research was conducted at PT XYZ using the Waterfall development method. Data were collected through observation, interviews, and documentation studies to formulate system requirements. The system design was modeled using Unified Modeling Language (UML), including use case diagrams and activity diagrams, which illustrate the interaction flows between employees and administrators. The implementation results show that the system successfully validates attendance location, stores photos as visual evidence, and facilitates administrators in managing employee and location data. Testing using the Black Box method confirmed that all functions operated as expected. Thus, the system improves the validity of attendance data, reduces fraud, and supports administrative efficiency within the company.